KEMAMPUAN GURU DALAM MENINGKATKAN KREATIVITAS BELAJAR SISWA KELAS XI IPS PADA MATA PELAJARAN EKONOMI SMPN 1 PANGEAN - Hartanto, Dicki; Anderiyani, Eka Seftiyana (Perspektif, 2015)
The study consisted of one variable, it was teacher’s ability in improving student’ learning creativity. The purpose of study was to find out how teacher’s ability in improving students’ learning creativity of eleventh year students of social studies at economic subject at SMP N 1 Pangean. The subject of study was the teacher of economic for eleventh year students of social studies at economic subject at stat senior high school 1 Pangean and the object was teacher’s ability in improving students’ learning creativity of eleventh year students of social studies at economic subject at SMP N 1 Pangean. The population of study was a teacher of economic for eleventh year students of social studies at economic subject at SMP N 1 Pangean. The writer did not take any sample for the population of study was not few so the study was called by population study. The data of study were collected using questionnaires and documentation. The data which have been collected were qualitative data and some of them were quantitative data and all data were analyzed with descriptive qualitative analysis technique with percentage. The conclusion of study were that teacher’s ability in improving students’ learning creativity of eleventh year students of social studies at economic subject at SMP N 1 Pangean was categorized “good” with the percentage was 75.75% and this number in the range of 61%80%..